The Multiethnic Slavery Institution through the Eyes of Western Women and 'the real position of women in the religious system of Islam' - Irene Kamberidou (Media, Religion and Gender in Europe, 2015)
This chapter has shown that the multiethnic harem slavery institution was the Ottoman system’s primary socialization agent and an indispensable part of its self-reproduction. It has contributed to the discourse on sexual slavery, primarily through the first-hand accounts of western women and harem inmates of the 19th century. It has shown that multiethnic–multiracial slavery was vital for the Ottoman economy and social system and provided a means of social integration-assimilation and social mobility: status and political power. Sexual slavery was a central part of the slave system and slaves of both genders were easily integrated into Ottoman society, eventually becoming free Muslims.       Mainly through the eyes of western women and harem inmates of the 19th century, corroborating that the harem system was based on slavery, this chapter has contributed additional evidence confirming that:  firstly, the expansionist views of Islam and the institution of slavery resulted in the multiethnic composition of the Ottoman households: harems and selemliks. Secondly, an Ottoman harem— especially that of the elite and so-called middle-class—was made up of women and children from different nations: Islamized slaves, liberated slaves and descendants of slaves, including islamized eunuchs. Thirdly, the Ottoman elite was responsible for the preservation of slavery until the early 20th century and, as a result, the prolongation of polygyny and the large-scale castration of African boys, which was another dehumanizing aspect of the Ottoman slavery institution.   Acknowledgments I would like to express my gratitude to the Greek artist Areti Kamperidis for her magnificent artwork, including her exceptional paintings, inspired by the female accounts and illustrated in this article. Keywords: human trafficking, slavery, sexual slavery, social mobility, polygyny, eunuchs, children’s harem, seraglio, marriage, divorce, veiling, gender, women WHEN CITING:  Kamberidou, I. (2015). The Multiethnic Slavery Institution through the Eyes of Western Women and 'the real position of women in the religious system of Islam'. In Miriam Diez Bosch and Jordi Sanchez Torrents (eds). Media, Religion and Gender in Europe (pp. 53-79). Barcelona: Blanquerna Observatory on Media, Religion and Culture. Faculta de Comunicatio i Relacions Internacionals Blanquerna,Universitat Ramon Llull.                     [Α.1. in Apella]